Finding Needle in the Haystack: “Kasur’s Bogeyman” Brought to Justice by Geographic Profiling and Mass DNA Screening - Muhammad Ahsan Butt (Instituto Paulista de Estudos Bioéticos e Jurídicos, 2021)
This article describes the application of the concept of geographic profiling in hunting a serial child rapist in Kasur, Pakistan. It also discusses, how DNA became the prime witness against the serial rapist in the court of law. In January 2018, the blind rape and murder case of Zainab Amin hit the headlines. Following autopsy and the subsequent forensic examination, the only piece of evidence, the agencies had, was the DNA profile of the perpetrator and the information that the source of DNA profile is a serial child rapist, involved in at least seven more cases. The analysis of all crime sites and the distance between them strongly suggested that the offender most likely was a local resident. Mass DNA screening in the target region was conducted by CSI teams of Punjab forensic science agency. The DNA matched with suspect number 814 who later confessed all his crimes. In Polygraph examination, the offender revealed his modus operandi which was in line with the hypotheses made during the geographic profiling of the crime scenes. Thus, geographic profiling proved to be a very useful investigative tool in predicting the probable location of the criminal involved in a series of crimes.